Solidification of heavy metals using cement and rice husk ash - Chang, Ching-lung; Ahn, Kyu-Hong; Krienqsak Udomsinrotm; Verink, Johan; ROC Government (Bangkok : Asian Institute of Technology, 1989)
A ceme n t-silica based technique wa s us ed for waste stabilization. Ordinary Portland Cement < OPC), Portland Rice Husk As h Cement CPRHAC) are used as ce mentitious binders in this experi me nt. Synthetic wastes containing Cr, Cu and Hg are prepared in laboratory. Heavy Metal Bonding Mechanisms are points to explain the leaching behavior. types between metal and binders result trends: Cr leachability wa s higher in PRHAC and Hg leachability were higher in OPC experi ment. found to be the key The diff ere nt bonding in diff ere nt leaching than in OPC, while Cu than in PRHAC in this Cu and Hg bonding with binders is a kind of pore trapping or pores s urfaces adsorption, so their leachability we r e affected b y alkalinity, the h igh er alkalinity, the mor e leachability. Comparing OPC - based method and PRHAC - bas e d method in this study, it was found out that OPC was better immobilizer for Cr, while PRHAC was better immobilizer for Cu a nd Hg .
A thesis submitted in partial fulfillment of the requirements of the degree of master of engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Hazardous wastes